Self-Disclosure Tendencies in Digital Spaces: A Qualitative Study of Secondary Instagram Account Use Among Guidance and Counseling Students - Yuttami Keila Azahra; Agus Triyanto (ProGCouns: Journal of Professionals in Guidance and Counseling, 2026)
This research focuses on the self-disclosure of students from guidance and counseling studies who use a second Instagram account. Data Analysis Approach A thematic analysis was conducted on the qualitative data following the six-phase model proposed by Braun and Clarke (2021). Participants were recruited using purposive sampling with explicit inclusion criteria: active Guidance and Counseling students who had owned a second Instagram account for at least 1 year prior to data collection and who frequently used the account to communicate thoughts, feelings, and daily life experiences. Seven participants met all criteria. Theoretically, this study is based on Goffman's Dramaturgy Theory and Butler's Performativity theory as an interpretative framework of the second account use situation regarding identity performance and self-presentation in a digital context. The analysis yielded five themes based on DeVito's (2011) categories of self-disclosure: Amount, Accuracy, Intention, Intimacy, and Valence. Results indicate that the second Instagram account serves as a negotiated backstage space, where Guidance and Counseling students express identities that are context-dependent, emotionally oriented, and relationally selective, all of which have implications for developing empathic and reflexive counselor competencies. Counselor education implications and Guidance and Counseling service development are also discussed in the article.